PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN RESTORAN KARIBIA SEAFOOD MEDAN - Dinda Syahri; Muhammad Iqbal Pratama; Yesy Gustiara (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2018)
A business that is growing very rapidly is a food business or known as culinary, one of the culinary places is a restaurant. A restaurant is an effort to provide food and beverage services equipped with equipment and equipment for the process of making, storing and serving in a fixed place that does not move. To give satisfaction to consumers, companies must be able to sell goods or services with the best quality at a reasonable price in accordance with what is obtained. The company also carries out strategies to shape customer satisfaction by providing quality services. With good quality will encourage consumers to establish good relations with companies such as the Caribbean Seafood restaurant Medan. This study aims to determine the effect of product quality and service quality on customer satisfaction Caribbean Seafood Medan restaurants. This research method uses descriptive quantitative methods. The study population was 35 Caribbean Seafood Medan consumers. The results of this study indicate that customer satisfaction occurs due to a positive and significant influence on the two independent variables tested, namely product quality and service quality to customer satisfaction through t test and F test, while the R Square number shows 96.6% is a variation of satisfaction consumers of the Caribbean Seafood Medan restaurant which can be explained by the two independent variables, the rest explained by other factors outside of this study.